Ammonium to total nitrogen ratio affects the purslane (Portulaca oleracea L.) growth, nutritional, and antioxidant status - Chrysargyris, Antonios; Hajisolomou, Efraimia; Xylia, Panayiota; Tzortzakis, Nikos G. (My University, 2023)
Purslane (Portulaca oleracea L.) is a widespread weed, which is greatly appreciated for its high nutritional value. The present work evaluated the effect of different ammonium/total nitrogen ratios (NH4/Total N: Nr 0.01-0.15) on growth, physiological and biochemical parameters, and nutrient accumulation in different plant parts of hydroponically grown purslane, under two growing seasons, spring and autumn. Young seedlings of purslane were transferred to a Nutrient Film Technique (NFT) system and they were exposed to different Nr levels. The pH and the electrical conductivity of the nutrient solution were kept constant at 5.8 and 2.3 mS cm-1, respectively. After the end of the cultivation periods (19 days for spring and 22 days for autumn), a series of assessments (growth parameters, mineral content in different plant organs, antioxidant status of the plant, etc.) were done. Plant height, leaf number, root fresh weight and plant biomass revealed decreased trends at the higher NH4/total N ratios, especially during the autumn growing season. Total phenols, flavonoids and antioxidant capacity appeared increased at Nr ≤ 0.10 during both seasons (autumn and spring), revealing higher nitrogen accumulation rates and increased water and nutrient use efficiency. Purslane plants grown in Nr 0.05-0.10 revealed a less intense oxidative stress, with decreased lipid peroxidation levels that was the result of the activation of both enzymatic (superoxide dismutase, catalase and peroxidase) and non-enzymatic (ascorbic acid) antioxidant capacity of the plant. Increased Nr resulted in the accumulation of potassium, while calcium and magnesium levels in leaves were decreased. Additionally, the greater water use efficiency was measured for plants grown under Nr 0.01-0.05. Therefore, the recommended ammonium/total nitrogen ratio for purslane production of increased yield, improved nutritional value and efficient use of water and nitrogen sources is to employ Nr of 0.05, while additional care should be addressed during autumn periods as plants are subjected to greater impacts of the Nr ratio.
Keywords: Ammonium to total nitrogen ratio; Antioxidants; Mineral fertilizer; Purslane; Soilless culture